Attributes of nanoparticles obtained by green synthesis for application in antifungal coatings - Gámez Espinosa, Erasmo Junior (2018)
The green synthesis of nanoparticles based on the use of aqueous vegetable extracts islow cost, non-polluting and makes use of renewable reagents. These extracts containmetabolites that perform as reducing and stabilizing agents. In this regard, the use oftannins is promising due to their high polyphenol content. The present work proposes tosynthesize and characterize nanoparticles obtained silver and copper salts with ?tara?tannin (TT). TT is commercially available and proceeds aqueous extract of Caesalpiniaspinosa. The nanoparticles were obtained starting an aqueous solution of AgNO3 10-2 Mand Cu(NO3)2.3H2O 10-2 M to which the tannin solution was added in constantagitation. Three concentrations of TT were used: 500, 1000 and 2000 ppm. This processwas done at 60° C and pH = 7. The stability over time of these nanoparticles wasevaluated by UV-vis spectroscopy carried out at different times: 1, 30 and 60 days. Toconfirm the obtaining of the nanoparticles and observe their morphology, transmissionelectron microscopy (TEM) was applied. The synthesized nanoparticles were purified andFourier transform infrared spectroscopy (FTIR) was performed. The antifungal activity wasevaluated by the agar diffusion test (Kirby-Bauer) against the collection strains: Cladosporiumcladosporioides (MG731215), Alternaria tunuissima (MG731240) and Aspergillus versicolor (MG725821).UV-vis spectra of silver nanoparticles obtained TT solutions of 500 (NpsAg500), 1000 (NpsAg1000) and2000ppm (NpsAg2000) presented an absorption maximum around 400, 410 and 420 nm, respectively.These bands remained stable over time. In the case of copper salt the nanoparticles obtained with TTsolution of 2000ppm (NpsCu2000) showed a band at 330 nm and with 1000 and 500ppm resultedunstable. TEM micrographs confirmed the presence of quasispherical nanoparticles predominantlysmaller than 20 nm with higher frequency. FTIR spectra confirmed the strong interaction between ofthe nanoparticles and the tannin used in the synthesis. Related to the agar diffusion test, NpsCu2000was not active against the fungal strains used while the silver nanoparticles showed to be active inall cases. In this sense, NpsAg500 presented the highest inhibition zone against C. cladosporioides. Thenext step will be to formulate coatings with these nanoparticles.